Komunikasi Efektif dengan Workshop Penggiat Pencegahan, Pemberantasan Penyalahgunaan, dan Peredaran Gelap Narkoba (P4GN) di Masyarakat - Syahferi Anwar; Balqis Nurmauli Damanik; Cut Roza Asminanda; Linawati Togatorop; Hely Hely (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The training for Activists in Prevention, Eradication of Abuse, and Control of Narcotics Trafficking (P4GN) in the Community with an Effective Communication Management Approach aims to enhance the capacity of activists in addressing narcotics issues through precise and effective communication techniques. This event was organized by BNN Langkat Regency on August 22, 2024, and attended by 15 participants, including members of community organizations, youth organizations, and local leaders from Desa Bersinar, Langkat Regency. The training featured lecturers from the Faculty of Health at Universitas Haji Sumatera Utara and the Public Health Study Program at Sekolah Tinggi Ilmu Kesehatan Columbia Asia as the academic speakers. The training methods included delivering materials in several sessions, with a focus on effective communication management following a break. The primary goal of this training is to equip participants with knowledge about P4GN and communication skills necessary for effectively disseminating anti-narcotics messages in a persuasive and informative manner. The expected outcomes of the training include enhanced participant capabilities in prevention, eradication, and control of narcotics trafficking within their communities and strengthened collaboration among various stakeholders.